Analisis Kebutuhan LKPD Berbasis Problem Based Learning pada Materi Struktur Atom untuk Kelas X Fase E SMA - Nofriyanti, Desi; Hardeli, Hardeli (YASIN, 2023)
Teaching materials play an important role in forming active and enjoyable learning. Therefore, the formation of teaching materials should be aligned with the learning model that will be used. This research aims to identify students' needs for problem based learning LKPD as teaching materials in learning activities. The method used in this research uses a descriptive method with a quantitative and qualitative approach. The data collection technique was through interviews with 2 chemistry teachers in Class X Phase E of SMA and distributing questionnaires to 55 students in Class X Phase E of SMA. The results of the interviews showed that teachers had never used problem based learning LKPD in learning activities. Apart from that, student learning outcomes are still low because students have difficulty understanding the learning material. The research results can be concluded that; 1) One of the teaching materials used by teachers in learning atomic structure is LKPD; 2) As many as 38% of students stated that the teaching materials used were not able to help them understand the material, as many as 95% of students were interested in using LKPD based on problem based learning; 3) Teaching materials in the form of LKPD based on problem based learning on atomic structure material need to be developed to support and maximize the learning process, as well as optimize learning activities.